2011
DOI: 10.1007/s10666-011-9304-0
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors and Risk Areas of West Nile Virus in Southern California, 2007–2009

Abstract: The West Nile virus (WNV) may post a significant health risk for mammals, including humans and insects. This study examines the spatial-temporal effects of environmental factors on WNV dissemination with a case study of ten counties in the southern California, where the epidemic was recently most prevalent within the USA. WNV surveillance data were obtained from the California Vectorborne Disease Surveillance System and Centers for Disease Control and Prevention. Remote sensing and Geographic Information Syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 56 publications
2
7
0
Order By: Relevance
“…In this study, the environmental factors temperature and precipitation were significantly related to the incidence of human West Nile cases, and this finding is consistent with previous studies (12,14,31,32). Mosquitoes need water for larvae to develop, and insects grow more rapidly in warmer temperatures (3335).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, the environmental factors temperature and precipitation were significantly related to the incidence of human West Nile cases, and this finding is consistent with previous studies (12,14,31,32). Mosquitoes need water for larvae to develop, and insects grow more rapidly in warmer temperatures (3335).…”
Section: Discussionsupporting
confidence: 93%
“…Several variables that previous studies found associated with WNV include temperature, rainfall, and habitat. In southern California, summer mean temperature, land surface temperature, elevation, landscape diversity, and vegetation water content were principle environmental factors that contributed to WNV propagation (12). High temperature has been consistently associated with outbreaks of WNV (13).…”
Section: Introductionmentioning
confidence: 99%
“…In their study in northern Colorado, Eisen et al . [76] found that mosquito species richness is highest in plains habitats at elevations below 1,600 m. Later, Liu and Weng [77] showed in southern California that areas with lower elevations tended to be more susceptible to WNV invasion. This finding may be explained by the higher landscape diversity usually associated with multiple land cover types such as urban, grass, and water.…”
Section: Environmental Driversmentioning
confidence: 99%
“…Spectral indices acquired from satellite imagery provide information about environmental characteristics like temperature, vegetation cover, and moisture (Rodgers & Mather, 2006). Liu & Weng (2012) in a study on WNV risk in southern California found that one of the main factors contributing to the WNV propagation included land surface temperature. They related higher temperature to viral replication in mosquitoes for WNV to be disseminated throughout the year.…”
Section: Introductionmentioning
confidence: 99%